A Comparative study of haemodynamic effects between two different doses of oxytocin in lower segment caesarian section under spinal anaesthesia - Zainudin, Asmah (2013)
A comparative study of haemodynamic effects between two different doses of oxytocin in lower segment caesarean section under spinal anaesthesia. There is always a discussion within the obstetric anaesthesia community about the correct dose of oxytocin and its method of administration. Oxytocin may cause adverse cardiovascular effects, including tachycardia and hypotension, whereas an inadequate dose can result in increased uterine bleeding. We compared the effects of two doses of oxytocin in a randomised doubleblind trial. Seventy patients undergoing elective lower segment caesarean section received an intravenous bolus of either 10 unit or 2 unit of oxytocin after cord clamping. followed by oxytocin infusion 10 unit per hour. All patients received spinal anaesthesia. phenylephrine was used if the blood pressure fell more than 15% from the baseline. We compared changes in heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, uterine tone, blood loss, additional usage of uterotonic drugs and emetic symptoms. There was a larger decrease in MAP in patients who received 10 unit, MD — 12.54 mmHg (15.1%), p value <0.0001 than in those who received 2 unit, MD= - 5.46 mmHg (7.1 %), p value = 0.023 There was a greater increase in mean heart rate in patients who received 10 unit , MD - +9.20 bpm (10.2%), p value <0.0001 than in those who received 2 unit , MD= -+8.23 bpm (9.5%), p value = 0.004. Maximum increase in HR was at 2 minutes (+15.57 bpm, 17.28%).The frequency of antiemetic use was higher after 10 unit (27.6%) than 2 unit (2.9%), (/?=0.042). There was no difference in blood loss, uterine tone, or request for additional uterotonic drugs in both groups. In elective lower segment caesarean under spinal anaesthesia with low risk for post-partum haemorrhage, a 2 unit bolus of oxytocin results in less haemodynamic changes than 10 unit, with less nausea and no difference in uterine tone, estimated blood loss and the need for additional uterotonics drugs.